Digital Product Management - Brennan, Kevin J.; Godwin, Sallie; Hendrickx, Filip (BCS, The Chartered Institute for IT, 2022)
The growth of digital media, products and services has resulted in a change in the way companies do business. With technology moving to the forefront and consumers demanding simplicity, companies have increasingly turned to product managers to deliver an end-to-end, integrated product experience.With this practical guide, you'll learn how to understand the needs of external customers without requirements elicitation or sign-offs, the difference between customer and business value, and why your product needs to create both. You'll discover how to respond to changes in the market and the actions of competitors. You'll understand how to develop new products, launch them into the market and how to deliver business outcomes through the maturity of your product. You'll also explore how to manage for results, through managing by influence, creating a supportive team culture and managing your own time.